2012
DOI: 10.5296/jbls.v3i1.1421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aluminium Chloride Exposure on the Histology of the Cerebral Cortex of Adult Wistar Rats

Abstract: AbstractsAluminium (Al) is presents in many manufactured foods, medicines and is also added to drinking water for purification purposes. Human exposure to Al has been increasing over the last decades. Al exposure and neurological impairments demonstrate mixed findings. The cerebral cortex is a sheet of neural tissue that is outer-most to the cerebrum of the mammalian brain and it plays a key role in memory, attention, perceptual awareness, thought, language, and consciousness.The objectives of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 31 publications
12
19
0
Order By: Relevance
“…Epidemiological studies have indicated a link between aluminum in drinking water and AD. A variety learning and memory deficits (Buraimoh, Ojo, Hambolu, & Adebisi, 2011;Yokel, 2000). Aluminum chloride was implicated to have negative effects on anxiety-related behavior of rats as it increased the rate of anxiety, neurodegenerative effects of cerebral cortex of adult rats especially at higher dose, and detrimental effects on the integrity of the testes of rats (Buraimoh et al, 2011(Buraimoh et al, , 2012Narahyana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have indicated a link between aluminum in drinking water and AD. A variety learning and memory deficits (Buraimoh, Ojo, Hambolu, & Adebisi, 2011;Yokel, 2000). Aluminum chloride was implicated to have negative effects on anxiety-related behavior of rats as it increased the rate of anxiety, neurodegenerative effects of cerebral cortex of adult rats especially at higher dose, and detrimental effects on the integrity of the testes of rats (Buraimoh et al, 2011(Buraimoh et al, , 2012Narahyana et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A variety learning and memory deficits (Buraimoh, Ojo, Hambolu, & Adebisi, 2011;Yokel, 2000). Aluminum chloride was implicated to have negative effects on anxiety-related behavior of rats as it increased the rate of anxiety, neurodegenerative effects of cerebral cortex of adult rats especially at higher dose, and detrimental effects on the integrity of the testes of rats (Buraimoh et al, 2011(Buraimoh et al, , 2012Narahyana et al, 2014). Human exposure to aluminum occurs primarily through ingestion of food and water, utilization of personal care products and cookware, and consumption of medications and administered vaccines (Saiyed &Yokel, 2005;Seubert, Monaci, Pizza, O'hagan, & Wack, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium (Al) is one of such metals frequently distributed through earth crust [3]. It is an integral component of many medicines, food additives and also added to drinking water for purification purposes [4]. Several sources of aluminium in daily life include spices, yellow cheese, aluminum ware, corn, salt, cosmetics, herbs, tea, antacid drugs and tooth paste [5].…”
Section: Introductionmentioning
confidence: 99%
“…alters behaviour), have negative effects on anxiety-related behaviour of wistar rats as it increased the rate of anxiety in aluminium treated rats, had neurodegenerative effects on the histology of cerebral cortex of adult wistar rats especially at higher dose, was also said to have detrimental effects on the integrity of the testes of wistar rats , and also decrease the level of sperm count, but did not result into infertility. [16][17][18][19][20].This study was aimed at evaluating the possible effects that aluminium chloride could have on the histology of the liver of adult wistar rats.…”
Section: Introductionmentioning
confidence: 99%